Ambiguity as agency: critical opportunists in the neoliberal city - Kaethler, Michael; De Blust, Seppe; Devos, Tim (CoDesign, 2017)
Participatory design and planning processes are subject to co-option by neoliberal forces and post-political logics. This places participatory practitioners, such as co-designers or planners involved in co-production in a difficult position, whereby not taking a critical stance can lead to legitimising and normalising the dominant logic of the state or elite. However, taking a clear critical stance can result in a loss of access and trust from stakeholders and ultimately result in being side-lined from influential design or planning processes. This article critically adapts Eric M. Eisenberg's theory of strategic ambiguity for the post-political context as a potential discursive resource for practitioners seeking to remain active within influential urban decision-making processes while sustaining a critical position and practice. It opens a discussion with the participatory practitioners ndvr on their use of ambiguity and how it negotiates a balance between access, trust and criticality.